ASSOCIATION OF AGE AND GENDER WITH VENTRICULAR LATE POTENTIALS IN PATIENTS WITH MITRAL VALVE PROLAPSE - Khan, Muhammad Alamgir; Majeed, Syed Muhammad Imran; Shabbir, Faizania; Ahmed, Tausif (Pakistan Journal of Physiology, 2014)
Background: Ventricular late potentials are extremely low amplitude and high frequency cardiac signals which are not detected by standard 12-lead ECG. These potentials have been established as non-invasive markers of ventricular arrhythmias. These parameters may be associated with the genesis of ventricular late potentials. This study was planned to investigate this relationship in patients with mitral valve prolapse. Methods: Thirty-seven patients with mitral valve prolapse were recruited through convenience purposive sampling. Patients of both the gender and any age were included in the study whereas those with acute or old myocardial infarction, diabetes mellitus and hypertension were excluded. Ventricular late potentials were determined using SAECG recording machine according to the standard criteria. Results: There were 23 men and 14 women aged 26.27Â±6.18 years. Nine (6 men and 3 women) patients had ventricular late potentials and the remaining (17 men and 11 women) were without these potentials. There was no association of age and gender with ventricular late potentials (p>0.05). Conclusion: Age and gender are not associated with ventricular late potentials in patients with mitral valve prolapse. Pak J Physiol 2014;10(3-4):3â€“5